Between Strategy and Governance: Which Matters More in Driving Tax Disclosure? - Ulynnuha, Ovi Itsnaini; Millati, Nabila Fida; Mujiyati; Aris, Muhammad Abdul; A'zizah, Laila Oshiana Fitria (Riset Akuntansi dan Keuangan Indonesia, 2025)
This study aims to examine the effect of tax planning, board of commissioners size, and independent commissioners on tax disclosure among manufacturing firms in Indonesia. The research employed a quantitative approach using panel data regression with 38 firm-year observations from 19 listed companies that recently listed their IPOs since the period 2022–2023. The analysis was conducted by estimating the Common Effect, Fixed Effect, and Random Effect models, followed by specification tests such as Chow and Hausman. The Random Effect Model was identified as the most appropriate model. The empirical results indicate that tax planning has a positive effect on tax disclosure at the 10% significance level, while the size of the board of commissioners has a positive and significant impact at the 5% level. In contrast, the presence of independent commissioners does not show a significant influence. These findings highlight the importance of board size and tax strategies in improving corporate transparency, while also suggesting that the effectiveness of independent commissioners requires further attention in the Indonesian context.